(The extent to which interference in internal affairs for humanitarian reasons, affected the principle of sovereignty (A study of jurisprudence in the light of contemporary international law - Ahmed, Abker Ali Abdul Majeed (Arab Journal for Sciences and Research Publishing, 2017)
This research paper explored the effect of interference in internal affairs for humanitarian purposes on sovereignty principle (Jurisprudence study according to contemporary international law). The research problem was the existence of a right for states and international organizations to monitor and enforce respect of human rights to ensure that weather the transaction is legal or not. The research significance is to explore to what extent international interference for humanitarian purposes affects sovereignty principle considering that humanitarian interference conflicts with some international legal systems and has reflects on sovereignty principle like the principle of noninterference in internal affairs, the princely of equality in sovereignty, and the principle of restricting power usage or threating to use it, which included in the UN character. The study aimed at exploring the legal effects of International interference for humanitarian purposes on the sovereignty principle, and on the principle of noninterference in internal affairs according to the international contemporary law. The researcher adopted the descriptive, analytical, inductive and historical approaches. The researcher concluded to find that human rights are part of the international commitments and are not internal affair which restricts states and international organizations to monitor, because monitoring is the core of the state commitment to apply these conventions. Human rights principles according to contemporary legal aspects adopted by the UN became an international issue not internal, and that depends on considerations related to public interest. The researcher recommended states to put international conventions and declarations related to human rights into execution in order not make it a justification as internal affairs when it has been interfered. He also recommended to consider any interference without the UN acceptance or under its control as illegal, and to consider it as aggressive transaction according to UN character and according to Rome statute which established the ICC.